Born to hang [large type] - McCauley, Terrence (McCauley, Terrence. Jeremiah Halstead western, 2023)
"Jeremiah Halstead knew it would be hard to uphold the law in a buckwild boomtown like Silver Cloud, Montana. He also knew it would be easy to make some dangerous enemies. But he never counted on a foe as flat-out evil as Ed Zimmerman. This cold, conniving cutthroat may be awaiting trial, but the outlaw bounty he placed on Halstead's head is still in effect. Warrants have been issued for Halstead's arrest -- and even his once-close friends are looking to put the blast on him. Forced into hiding in the harsh Montana wilderness, Halstead has no choice but to trust a group of friendly trappers. But as he quickly learns, some friendships come with a price. And sometimes that price comes high -- with death. Alone. Desperate. Hunted like an animal. Deputy U.S. Marshal Jeremiah Halstead is about to face his day of judgment. But he won't do it alone. He will reach out to the last person he can trust -- his former partner -- and greet that fateful day with blood and agony" --